Energy considerations in groundwater-ridging mechanism ofstreamflow generation - Waswa, George W; Lorentz, Simon A. (Hydrological Processes, 2015)
Groundwater ridging is the rapid rise of a shallow water table during a rainfall event, in an environment where, in the pre-event period, the capillary fringe extends to the ground surface. Groundwater ridging is widely cited to account for the observed significant appearance of pre-event water in a stream stormflow hydrograph. Various hypotheses have been advanced to explain the groundwater-ridging mechanism; and most recently, from afield study site in South Africa, an energy hypothesis was proposed, which explains that groundwater-ridging water-table rise is a result of rapid introduction and transmission of additionalpressure head into the capillary fringe from an intense rainfall at the ground surface. However, there is a need for further analysisand evidence from otherfield study sites to confirm and support this newly proposed energy hypothesis. The objectives of thispaper are, therefore, as follows: to review previous observations on groundwater ridging, from other study sites, in order todeduce evidence of the newly proposed energy hypothesis; to present and evaluate a one-dimensional diffusion mathematicalmodel that can simulate groundwater-ridging water-table rise, based on the newly proposed energy hypothesis; and to evaluatethe importance of a capillary fringe in streamflow generation. Analysis of previous observations from other study sites generally indicated that the rate of groundwater-ridging water-table rise is directly related to the rainfall intensity, hence confirming and agreeing with the newly proposed energy hypothesis. Additionally, theoretical results by the mathematical model agreed fairly well with the field results observed under natural rainfall, confirming that the rapidly rainfall-induced energy is diffusively transmitted downwards through pore water, elevating the pressure head at every depth. The results in this study also support the concept of a three-end-member stream storm flow hydrograph and contribute to the explanation of how catchments can store water for long periods but then release it rapidly during storm events
Keywords: capillary fringe; diffusion mathematical model; potential energy; pressure head; rapid water-table response